(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Philip Larkin is often characterized as a poet of existential gloom, exploring themes of mortality, isolation, and the passage of time. However, his poetry also contains moments of optimism, offering brief but significant glimpses of light amid the shadows. This paper examines these moments of hope and affirmation within Larkin’s body of work, demonstrating how they function as counterpoints to his prevailing melancholic themes. Through close readings of selected poems, this study highlights the ways in which Larkin’s use of imagery, tone, and structure creates fleeting yet profound expressions of joy, wonder, and human connection. Poems such as The Trees, Coming, and Born Yesterday showcase Larkin’s ability to capture renewal, simple pleasures, and quiet optimism despite his characteristic skepticism. By focusing on these elements, this paper challenges the conventional perception of Larkin as an exclusively pessimistic poet and argues for a more nuanced understanding of his work. Furthermore, this paper situates Larkin’s moments of optimism within the broader context of post-war British poetry, considering how his ambivalence toward modernity and tradition contributes to his complex emotional landscape. Ultimately, this study reveals that Larkin’s poetry, while often shadowed by existential concerns, also acknowledges the possibility of beauty, renewal, and fleeting happiness, thereby enriching its emotional depth and philosophical scope.